G. Bromley Oxnam papers - Oxnam, G. Bromley (Garfield Bromley), 1891-1963.
Correspondence, diaries, sermons, addresses, lectures, writings, articles, book reviews, clippings, scrapbooks, photographs, and other papers concerning Oxnam's life and career in religious and public service. Documents his work with the Church of All Nations, the controversy over diplomatic relations between the U.S. and the Vatican, the issues of church and state and Protestantism as it related to Catholicism, charges made by the House Committee on Un-American Activities against Oxnam, and his life as reported by the press.
Correspondents include George Smith Brown, Samuel McCrea Cavert, Matthew J. Connelly, Henry Hitt Crane, John Foster Dulles, Sherwood Eddy, Dwight D. Eisenhower, Franklin Clark Fry, Frederick Brown Harris, Cordell Hull, Donald Lester Jackson, David Eli Lilienthal, Carl McIntire, Marvin Hunter McIntyre, Louie D. Newton, Charles C. Parlin, Daniel A. Poling, Eleanor Roosevelt, Franklin D. Roosevelt, Henry Knox Sherrill, William L. Stidger, Henry L. Stimson, Myron Charles Taylor, Harry S. Truman, Harold Himmel Velde, Henry A. Wallace, Herbert Welch, and Athenagoras I, Ecumenical Patriarch of Constantinople.
Methodist clergyman and theologian.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Athēnagoras -- I, -- Ecumenical Patriarch of Constantinople, -- 1886-1972 -- Correspondence; Brown, George Smith -- Correspondence; Cavert, Samuel McCrea, -- 1888-1976 -- Correspondence; Connelly, Matthew J., -- 1907-1976 -- Correspondence; Crane, Henry Hitt, -- 1890-1977 -- Correspondence; Dulles, John Foster, -- 1888-1959 -- Correspondence; Eddy, Sherwood, -- 1871-1963 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Fry, Franklin Clark, -- 1900-1968 -- Correspondence; Harris, Frederick Brown, -- 1883-1970 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Jackson, Donald Lester, -- 1910-1981 -- Correspondence; Lilienthal, David Eli, -- 1899-1981 -- Correspondence; McIntire, Carl, -- 1906-2002 -- Correspondence; McIntyre, Marvin Hunter, -- 1878-1943 -- Correspondence; Newton, Louie D. -- 1892-1986 -- Correspondence; Parlin, Charles C. -- 1898- -- Correspondence; Poling, Daniel A. -- 1884-1968 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Sherrill, Henry Knox, -- 1890-1980 -- Correspondence; Stidger, William L. -- 1886- -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Taylor, Myron Charles, -- 1874-1959 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Velde, Harold Himmel, -- 1910- -- Correspondence; Wallace, Henry A. -- 1888-1965 -- Correspondence; Welch, Herbert, -- 1862-1969 -- Correspondence; United States. -- Congress. -- House. -- Committee on Un-American Activities; Catholic Church -- Foreign relations -- United States; Catholic Church -- Relations -- Protestant churches; Church of All Nations (New York, N.Y.); Church and state; Methodist Church -- United States; Protestant churches -- Relations -- Catholic Church; United States -- Foreign relations -- Catholic Church; Clergy; Theologians